Analisis Penggunaan Canva Dalam Pembelajaran PPKn Untuk Mengembangkan Sikap Berkebinekaan Global Dan Kemampuan Bernalar Kritis Siswa SD Kelas IV - Abdullah Abdullah; Maisura Maisura; Muhammad Iqbal (Jurnal Ilmiah Global Education, 2026)
This study aims to examine the effectiveness of using Canva as a digital learning medium in Civics Education (Pancasila and Citizenship Education) for developing global diversity awareness and critical thinking skills among fourth-grade elementary school students. The research was conducted at SD Negeri 3 Nisam Antara using a qualitative descriptive approach with a project-based learning design. Data were collected through classroom observations, student activity records, performance assessments, and documentation of learning products created using Canva, including posters, infographics, presentations, videos, and campaign materials. The findings indicate that the systematic integration of Canva significantly enhanced student engagement and learning quality. Student participation increased markedly, with all students actively involved in learning activities and an overall implementation score categorized as very good. The use of Canva effectively developed students’ global diversity competence across cognitive, affective, and behavioral dimensions, reflected in improved understanding of cultural diversity, increased empathy and tolerance, and positive collaborative behaviors in heterogeneous groups. In addition, students’ critical thinking skills improved substantially across key indicators, including questioning ability, distinguishing facts from opinions, constructing logical arguments, synthesizing information, and proposing creative solutions. The study concludes that Canva functions not merely as a presentation tool but as a meaningful pedagogical medium that facilitates the integrated development of character values and higher-order thinking skills. This research demonstrates that well-designed digital project-based learning using visual media can simultaneously strengthen global diversity awareness and critical thinking, contributing significantly to the realization of student character development in elementary education.